1999
DOI: 10.1148/radiographics.19.2.g99mr08399
|View full text |Cite
|
Sign up to set email alerts
|

Chemoembolization of Hepatic Neoplasms: Safety, Complications, and When to Worry

Abstract: Chemoembolization of the liver for unresectable malignancy, although controversial, is being used with increasing frequency. Chemoembolization can be difficult, and there is great potential for causing complications. There are also findings after chemoembolization, particularly on computed tomographic scans, that may appear to indicate complications but are common and of no concern. Chemoembolization requires an understanding of the congenital and acquired variations of arterial anatomy that may be seen supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(54 citation statements)
references
References 26 publications
(32 reference statements)
0
52
0
1
Order By: Relevance
“…20 Hence, the presence of portal vein occlusion with or without hepatofugal flow was considered to be a significant contraindication in selection of patients for TAE and TACE therapy when these treatment modalities were first introduced. 5,[21][22][23] Clinical experience has shown that intraarterial hepatic regional therapies can be performed in the presence of PVT. Investigators have demonstrated that TACE can be performed safely in patients with PVT and cavernous transformation or patients with partial portal vein occlusion and hepatopedal flow providing modified techniques are used such as (1) low-dose, segmental; or (2) use of partial arterial occlusion as the endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…20 Hence, the presence of portal vein occlusion with or without hepatofugal flow was considered to be a significant contraindication in selection of patients for TAE and TACE therapy when these treatment modalities were first introduced. 5,[21][22][23] Clinical experience has shown that intraarterial hepatic regional therapies can be performed in the presence of PVT. Investigators have demonstrated that TACE can be performed safely in patients with PVT and cavernous transformation or patients with partial portal vein occlusion and hepatopedal flow providing modified techniques are used such as (1) low-dose, segmental; or (2) use of partial arterial occlusion as the endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact rate of cystic artery embolization remains controversial, recent reports have stated a much lower rate of 14% [12]. Though technological advancements in imaging equipment and familiarity with the procedure may account for some of the discrepancy, initial reports may have overstated the risks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the medical team caring for the patient must be well-versed in possible complications and likely toxicities in order to help the patient during a difficult recovery [123]. Careful selection of appropriate patients should be done to restrict the procedure to those who are likely to tolerate it and benefit from such an aggressive intervention.…”
Section: Resultsmentioning
confidence: 99%